Nii Kwei's Day - Provencal, Francis and McNamara, Catherine (Frances Lincoln Ltd, 2001)
Nii Kwei lives in Accra, the capital of Ghana. He gets up at 6 o'clock every morning. He helps his sisters and brother tidy up the compound, then he eats a breakfast ofcoco(corn porridge), bread, fried eggs and a chocolate drink. At 7:30 he goes to school in a taxi. Later, on his way home, he goes to Abraham's material store with his mother. He ends the day playing football with his cousins, back at the compound.
Keywords: Juvenile literature-Fiction